Civil Society: The Engine for Economic and Social Well-Being : The 2017 Griffiths School of Management and IT Annual Conference on Business, Entrepreneurship and Ethics (GMSAC) /: The 2017 Griffiths School of Management and IT Annual Conference on Business, Entrepreneurship and Ethics (GMSAC). ([2018]) - Universitatea Emanuel din Oradea., Facultatea de Management Griffiths and IT., Annual Conference on Business, Entrepreneurship and Ethics,
No abstract available